A conversation analysis of personal COVID-19 risk communication in a global pandemic: Presenter(s): Charlotte Albury, University of Oxford, United Kingdom. (April 2023) - Tremblett, Madeline; Webb, Helena; Begh, Rachna; Barnes, Rebecca; Lawrence, Wendy; Walmsely, Nicola; Groenewald, Deborah; Caunter, Marise; Patel, Dipti
Abstract : Background: Effective communication is key to ensuring people understand their risks of disease. Conversations between clinicians and patients provide good opportunity to discuss individual risk, including for COVID-19. During the height of the COVID-19 pandemic UK Foreign Commonwealth and Development Office (FCDO) clinical staff contacted members of British government teams working aboard to communicate their individual COVID-19 risk, supporting informed risk mitigation behaviours. Variation in the approaches used in these recorded telephone consultations provides unique opportunity to identify how personal COVID-19 risk was communicated, and to identify effective practices. Methods: Conversation analysis of 20 routinely recorded telephone consultations between FCDO clinicians and UK government staff, discussing COVID-19 risk. Calls were collected from September 2020 to July 2021, opportunistically sampled, and transcribed using the Jeffersonian approach. We used the next-turn proof-procedure to understand which approaches used by clinicians to communicate risk supported displays of understanding from patients. Results: We identified two ways clinicians achieved the complex activity of personal risk communication: (1) "Isolate risk" where a personal risk 'level' was stated (e.g. "your risks are low"), and often accounted for (e.g. "that's because of your age"); and (2) "Contextualised risk" where clinicians communicated a personal risk 'level', and an account. This was followed by describing a hypothetical scenario, tailored to an individual patient, placing risk in context. This was usually achieved through an 'if'-prefaced hypothetical (e.g "If you did develop COVID and you became very unwell there is a possibility that…if the local hospitals were overrun…we wouldn't be able to evacuate you"). Isolate risk communication was usually followed by minimal responses, whilst contextualised risk communication was often followed by displays of understanding (e.g. "I understand."). Discussion: When clinicians communicate personal COVID-19 risk to their patients, providing hypothetical scenarios, which place individual risk in context, may be most effective in supporting understanding.